Risk preference and rural livelihood transitions in the hilly and mountainous region of southern China: a case study in Ruijin City - Zhilong Wu; Hao Chen; Tian Zeng; Yushan Yan; Mengyuan Zhang (Scientific Reports)
Abstract Rural livelihood transition towards non-agriculturalization, non-grainization and even anti-urbanization has become a thorny social problem that undermines farmland resources and worldwide food security. Based on a simulation survey, this study explored the risk preferences and the livelihood transition mechanisms of typical farmers in the hilly and mountainous region. The results indicated that: (1) 76.86% of rural households exhibited risk aversion tendencies, with 60.67% being highly risk-averse. The ranking of risk aversion among the three typical farmers is consistent with asset abundance, with non-agriculture oriented households > semi-farmer and semi-labour households > vocational farmer households. (2) The non-grainization of vocational farmer households is significantly and positively correlated with the family labour force, land management area, and housing assets, yet negatively correlated with risk preferences. Compared to traditional grain cultivation, non-grainization in the hilly and mountainous region possesses lower risks and higher profitability for vocational farmer households. (3) The total non-agriculturalization of semi-farmer and semi-labour households correlates negatively with land management area but positively with family income. (4) Anti-urbanization and returning hometowns for farming are still regarded as a livelihood fallback by the non-agriculture oriented households, but excessive gift expenditure has become a heavy burden in rural society. Therefore, practical and systematical countermeasures are proposed in this research to guide sustainable livelihood transition.